75 How ACTIVE IS ACTIVE? physical Activity Levels in Children living with Obesity. (11th October 2021) - McClean, A; Gordon, J; McGoldrick, J; Long, A; Gawley, J; Harbinson, A; Khan, N; Graham, R; O'Connor, B
Abstract : Background and Aims: Physical activity is essential for healthy growth and development. Being active is an important tool for the prevention and treatment of childhood obesity. Physical activity can benefit children with obesity by helping them build a healthier body composition including stronger bones and muscles and increasing their energy expenditure. Other benefits for physical activity in children with obesity include improving mental wellbeing, sleep, gross motor skills and energy levels. The UK Chief Medical Officers (CMO) recommend that children aged 5-18 years should engage in moderate-to-vigorous intensity physical activity for at least 60 minutes per day. Moderate-to-vigorous intensity activities are defined as requiring effort and noticeably raising the heart and breathing rates. Examples include cycling, jumping and active play. This aim of this project was to assess physical activity levels in a population of children aged 5-16 years living with obesity and survey parental knowledge of the CMO guidelines. Methods: Families with a child aged 5-16 years living with obesity (defined by a BMI greater than the 98th centile on the RCPCH Growth Charts) were interviewed by a paediatric physiotherapist. Parents/carers were asked 3 questions. 'Do you consider your child to be physically active?' 'How many minutes of physical activity do you think are recommended by the UK CMOs for your child based on his/her age?' The third question was 'Can you describe your child's daily routine including any physical activities?' Families described their child's daily routine including play, sport, and active travel. Answers were recorded by the physiotherapist, anonymously complied, and analysed by the authors. Results: Families of 47 children living with obesity participated. 53% of parents/carers answered 'Yes' that they considered their child to be physically active. 47% answered 'No.' Only 19% of parents answered correctly when they were asked how many minutes of daily activity was recommended by the UK CMO. Upon analysis of the family accounts of their child's daily activities only 5 of the 47 children (12%) were achieving their daily physical activity targets. Conclusions: Encouraging children who are living with obesity to engage in physical activity is a fundamental treatment goal. This project highlights that a low percentage of children (12%) living with obesity are achieving the recommended daily activity levels. Many parents of children with obesity are not aware of the correct CMO recommendations for physical activity and overestimate how active their child is. As healthcare professionals we should promote and educate parents about the CMO recommendations.